Is the UK jumping or being pushed? British separatism after Cameron's EU veto - Andreas Maurer; Roderick Parkes (Stiftung Wissenschaft und Politik (SWP), 2012)
Since the December 2011 European Council, when the British prime minister blocked moves to amend the EU treaties, there has been speculation about a »domino secession«: the United Kingdom will break from the EU, causing Scotland to break with Britain. Any such British separatism would fly in the face of academic expectations: national groups that are heavily represented in the political process - as Scotland is in the UK, and the UK is in the EU - are usually deemed unlikely to reach for the exit. One particular strand of analysis might, however, explain these developments. Academics have shown that separatism at the periphery can be the result of exclusionary forces from the centre. Is British separatism a case of »secession by the centre«?
Keywords: 320